The Community Analytics Academy Pilot: A Community-Academic Partnership for Building Community Health Care Analytic Capacity - Rhonda BeLue; Lorinette Wirth; Amanda Steormer; Suzanne Alexander (SAGE Publishing, 2020)
The ability to analyze data to identify best practices is key to improving quality of care for community-based health care organizations (CBOs). Leading commercial statistical software remains too costly for many CBOs operating in underserved communities. The St Louis Integrated Health Network (IHN) collaborates with CBOs to increase access to health care. IHN and a local university developed the Community Analytics Academy (CAA), a training collaborative designed to meet the need for data-informed decision making among CBOs. Establishing analytics training collaboratives for CBOs empowers organizations to respond to the ever-growing amounts of health care data and the need for data-driven decision making.